Universal School-Based Screenings for Depression and Suicide: Identifying Students at Risk of Suicide. Issue 2 (28th February 2023) - Mirick, Rebecca G; Berkowitz, Larry; McCauley, James; Bridger, Joanna
Abstract: Schools have an important role to play in adolescent suicide prevention. This article describes universal screenings for depression and suicidality as one component of the Signs of Suicide (SOS) program in middle and high schools following the suicide death of a student in the past few years. Of the students screened ( N = 7, 429), 11.0 percent of youth were identified as at risk by the screening tool; 17.3 percent received a same-day secondary screen with a mental health professional. (Students without an at-risk screen could request a meeting with a mental health professional, so more students received secondary screenings than screened at risk.) Characteristics associated with an at-risk screen on the screening tool were identified. Girls were twice as likely to be identified as at risk than boys, and students exposed to a suicide death in the past year were 1.3 times more likely to have an at-risk screen. There was no difference in at-risk screens for middle versus high school students, but middle schoolers were more likely to receive a secondary screening due to help seeking from school staff. The article concludes with a discussion of the implications for school administrators at middle and high schools, including recommendations to screen with both a screening tool and an option to speak to an adult, strategies for planning for secondary screenings, and advantages to universal screening following the suicide death of a student.